Customary Criminal Dispute Resolution in Baduy Tribe Customary Law and Indonesian National Criminal Law - Muhammad Zahlan; Agus Hendrayadi; Sri Raharjo; Alam Suryo Laksono; Ade Saptomo (Universitas Sains dan Teknologi Komputer, 2024)
The research explores the resolution of customary criminal disputes in the context of the Baduy tribe, an ethnic group in Banten Province, Indonesia, with a focus on harmonization between local customary law and national criminal law. Through normative juridical methodology and analytical descriptive analysis, this study explores the mechanisms for resolving customary criminal disputes and their relationship with national criminal law. The results reveal the challenges in achieving harmony between traditional values and modern criminal law principles, as well as the implications for legal justice and human rights. The statutory approach and case approach help to comprehensively describe these dynamics, provide in-depth insight into the interaction between Baduy tribal customary law and Indonesian national criminal law and highlight the need for improved policies that are more inclusive and just.